Evaluasi Penyimpanan Obat di Gudang Instalasi Farmasi - Zahrin, Huwaidah Elza; Cholisah, Elis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the percentage of drug storage in the IFRS Sariningsih Warehouse in Bandung City that meets pharmaceutical storage standards. The method used is a type of descriptive research through data collection carried out observationally as an evaluation and suitability analysis. The research results show that the pharmaceutical warehouse consists of 2 rooms. One of the warehouses contains a work desk and computer, shelves used to store ointments, creams, capsules and tablets. Apart from that, there is also 1 (one) refrigerator. Another room is used to store medicines containing liquids. In this room there are shelves used to store medicines arranged by group, namely external use (topical), internal use (oral) and injection. Meanwhile, tablets, capsules and other dry medicines are stored in airtight containers and placed on shelves and in a separate room from liquids, ointments and injection preparations. Conclusion The suitability of drug storage conditions in the Sariningsih Hospital Pharmacy Installation Warehouse, reviewed with the suitability of CDOB as supporting data, can be said to be quite good. Keywords: Evaluation, Pharmacy Warehouse, Drug Storage.